Alveolar macrophages in lung cancer: opportunities and challenges - Chang, Cheng-Yen; Armstrong, Dominique; Corry, David B.; Kheradmand, Farrah (Frontiers in Immunology, 2023)
Alveolar macrophages (AMs) are critical components of the innate defense mechanism in the lung. Nestled tightly within the alveoli, AMs, derived from the yolk-sac or bone marrow, can phagocytose foreign particles, defend the host against pathogens, recycle surfactant, and promptly respond to inhaled noxious stimuli. The behavior of AMs is tightly dependent on the environmental cues whereby infection, chronic inflammation, and associated metabolic changes can repolarize their effector functions in the lungs. Several factors within the tumor microenvironment can re-educate AMs, resulting in tumor growth, and reducing immune checkpoint inhibitors (ICIs) efficacy in patients treated for non-small cell lung cancer (NSCLC). The plasticity of AMs and their critical function in altering tumor responses to ICIs make them a desirable target in lung cancer treatment. New strategies have been developed to target AMs in solid tumors reprograming their suppressive function and boosting the efficacy of ICIs. Here, we review the phenotypic and functional changes in AMs in response to sterile inflammation and in NSCLC that could be critical in tumor growth and metastasis. Opportunities in altering AMs’ function include harnessing their potential function in trained immunity, a concept borrowed from memory response to infections, which could be explored therapeutically in managing lung cancer treatment.